2019
DOI: 10.1093/jncics/pkz050
|View full text |Cite
|
Sign up to set email alerts
|

Toronto Workshop on Late Recurrence in Estrogen Receptor–Positive Breast Cancer: Part 1: Late Recurrence: Current Understanding, Clinical Considerations

Abstract: Disease recurrence (locoregional, distant) exerts a significant clinical impact on the survival of estrogen receptor–positive breast cancer patients. Many of these recurrences occur late, more than 5 years after original diagnosis, and represent a major obstacle to the effective treatment of this disease. Indeed, methods to identify patients at risk of late recurrence and therapeutic strategies designed to avert or treat these recurrences are lacking. Therefore, an international workshop was convened in Toront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…Therefore, its combination with a multigene assay is important for deciding whether to extend endocrine therapy (17,32). Furthermore, in addition to a clinical calculator, such as CTS5, and a multigene assay, further combination with an immunohistochemistry assay and radiographic imaging (computed tomography, positronemission tomography, and magnetic resonance imaging) or tumor marker assessments is important for predicting patient prognosis (25,33). In conclusion, although CTS5 was created to support decision-making by clinicians about extending adjuvant endocrine therapy in postmenopausal women with positive hormonal receptors, there are limitations in predicting late DR in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, its combination with a multigene assay is important for deciding whether to extend endocrine therapy (17,32). Furthermore, in addition to a clinical calculator, such as CTS5, and a multigene assay, further combination with an immunohistochemistry assay and radiographic imaging (computed tomography, positronemission tomography, and magnetic resonance imaging) or tumor marker assessments is important for predicting patient prognosis (25,33). In conclusion, although CTS5 was created to support decision-making by clinicians about extending adjuvant endocrine therapy in postmenopausal women with positive hormonal receptors, there are limitations in predicting late DR in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients who underwent CTS5 validation, GenesWell™ BCT also was applied, and the CTS5-derived risk group correlated with the gene assay risk group ( Supplementary Figure 1 ). However, the use of multigene assays is controversial in predicting late DR because some assays have not been validated, and the importance of clinical risk has been emphasized, especially in multigene panels of patients under 50 years of age ( 25 ). In conclusion, balanced application of a clinicopathologic prediction model and a multigene assay should be conducted to predict late DR, and further study is needed for proper selection of patients to receive extended adjuvant endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The two-year time horizon may confer additional limitations. Studies have shown that BC recurrence in estrogen receptor-positive (ER+) BC may have late recurrence [23][24][25]. However, it is rare that recurrence curves would cross over time and therefore it would be unexpected to see drastically different results over longer follow-ups.…”
Section: Limitationsmentioning
confidence: 99%
“…The subject of late recurrences was addressed in a focused international workshop held in Toronto (ON, Canada), in which several aspects of the question were examined [ 7 , 8 ]. Moreover, at the 2020 San Antonio Breast Cancer Symposium, an oral presentation in an educational session (E53) and a poster (PD9-11) further clarified research topics and clinical goals pursued in this area.…”
Section: Introductionmentioning
confidence: 99%